Association between oral dysbiosis and Parkinson’s disease: a systematic review - Murcia-Flores, Laura; Sánchez-García, Ana; Pecci-Lloret, María Pilar; Rodríguez-Lozano, Francisco Javier (Frontiers in Cellular and Infection Microbiology, 2025)
The oral cavity serves as the gateway to the human organism, hosting a diverse community of microorganisms that coexist in a state of symbiosis. Disruption of this balance leads to oral dysbiosis, a condition associated with infections and oral pathologies, which may contribute to the etiopathogenesis of systemic disorders such as Parkinson’s disease, a neurodegenerative movement disorder characterized by resting tremor, rigidity, and bradykinesia. While oral dysbiosis is recognized as a risk factor and an aggravating element for Parkinson’s disease, it is not regarded as a direct cause. This systematic review aims to synthesize existing research exploring the potential relationship between oral dysbiosis and the development of Parkinson’s disease. Following a comprehensive analysis, 12 studies were selected, comprising 11 case-control studies and one observational analytical study. These studies investigated the composition of oral microbiota in different sample groups, revealing a higher abundance of pathogenic oral bacteria in individuals diagnosed with Parkinson’s disease. The findings suggest that oral dysbiosis may influence both the onset of Parkinson’s disease and the progression of symptoms such as cognitive decline. These results pave the way for future research, particularly regarding alterations in oral microbiota as potential biomarkers for early diagnosis and disease monitoring.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024540056.